Understanding depression and mood disorders: implications for interventions in elementary children - Daviq Chairilsyah; Rita Kurnia (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Mood disorders, especially depression, are one of the most common mental health problems and have a broad impact on various aspects of elementary school students' lives. Depression not only affects emotional conditions, but also the sufferer's social function, work, and physical health. This article provides a comprehensive understanding of depression and other mood disorders, including symptoms, causes, risk factors, and treatment strategies. This study uses a literature study method by reviewing various scientific references, such as journals, books, and articles from trusted sources that discuss mood disorders from a psychological and medical perspective. The research results indicate that mood disorders have a complex and varied aetiology, involving biological, psychological, and environmental factors. Effective treatment requires a multidisciplinary approach, including psychotherapy, pharmacotherapy, and ongoing social support. The conclusion of this study emphasises the importance of early detection and appropriate intervention to prevent the long-term impact of mood disorders on the quality of life of elementary children.